2016
DOI: 10.1364/ol.41.000501
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties and highly efficient continuous-wave laser operation in Nd-doped Sr_1−xY_xF_2+xcrystals

Abstract: Spectral properties of Nd:Sr(1-x)Y(x)F(2+x) crystals were investigated. Compared with Nd:SrF2, the spectral parameters of Nd:Sr(1-x)Y(x)F(2+x) (x=0.05,0.1) were altered in a large scale. LD-pumped true CW laser has been demonstrated in the crystals. The slope efficiency up to 43.5% in 0.43% Nd:Sr0.95Y0.05F2.05 was achieved. The system is a promising candidate for highly efficient lasers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For example, the broadband materials of neodymium-doped glasses, , Ti:sapphire, Yb:YAG, Yb:S-FAP, and Yb:CaF 2 are widely adopted as gains in the ultrafast laser facilities. Recently, a large number of works on the ultrafast operations realized in the rare-earth-doped alkaline-earth fluoride crystals have been reported. It is because the rare-earth-doped fluorites have very broad emissions. , Due to the charge compensation effect, about twenty kinds of clusters were detected in the crystals . Various clusters and multisite characteristics make the photoluminescence inhomogeneously broadened, which makes the rare-earth-doped fluorites promising candidates for the generation of ultrashort pulses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the broadband materials of neodymium-doped glasses, , Ti:sapphire, Yb:YAG, Yb:S-FAP, and Yb:CaF 2 are widely adopted as gains in the ultrafast laser facilities. Recently, a large number of works on the ultrafast operations realized in the rare-earth-doped alkaline-earth fluoride crystals have been reported. It is because the rare-earth-doped fluorites have very broad emissions. , Due to the charge compensation effect, about twenty kinds of clusters were detected in the crystals . Various clusters and multisite characteristics make the photoluminescence inhomogeneously broadened, which makes the rare-earth-doped fluorites promising candidates for the generation of ultrashort pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al reported that the properties could be modulated continuously by Y 3+ ions, and a true continuous‐wave (CW) laser has been firstly implemented in Nd 3+ ,Y 3+ :CaF 2 crystal by incorporation of Y 3+ ions . Soon after, Laser based on Nd 3+ ,Y 3+ :SrF 2 crystal has been performed with slope efficiency of 43.5% by LD pumping . Pulses of 103 fs were obtained from LD pumped in Nd 3+ ,Y 3+ :CaF 2 single crystal by passively mode‐lock technique, then even shorter of 97 fs was implemented in Nd 3+ ,Y 3+ :SrF 2 …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Soon after, Laser based on Nd 3+ ,Y 3+ :SrF 2 crystal has been performed with slope efficiency of 43.5% by LD pumping. 7 Pulses of 103 fs were obtained from LD pumped in Nd 3+ ,Y 3+ :CaF 2 single crystal by passively modelock technique, 8 then even shorter of 97 fs was implemented in Nd 3+ ,Y 3+ :SrF 2 . 9 Besides Y 3+ , Sc 3+ , La 3+ , and Gd 3+ , Kaminskii tentatively used the solid solutions CaF 2 -SrF 2 containing Nd 3+ to tune the fluorescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…They achieved the slope efficiency near 15% at 1064 nm under LD pumping [16]. Recently, Ma et al achieved a CW laser with a slope efficiency up to 43.5% in Nd, Y:SrF 2 by LD pumping [17]. F Zhang et al demonstrated a dual-wavelength synchronously mode-locked Nd, Gd:CaF 2 laser for the first time [18].…”
Section: Introductionmentioning
confidence: 99%